PENGARUH KETERAMPILAN PROSES SAINS SISWA DENGAN MENGGUNAKAN MODEL PROJECT BASED LERANING PADA PESERTA DIDIK TERHADAP MATERI SEL KELAS XI DI ACEH BESAR - Mauizah Hasanah; Fatemah Rosma; Maulida Maulida; Vivi Yunisa Harahap (Jurnal Dedikasi Pendidikan, 2024)
This research aims to determined students science process skills using the PjBL model on cell material in class XI Dayah Insan Qur'ani Aceh Besar for academic year of 2023/2024. Data were collected in September 2023. The research method used was an experiment with a One Group Pretest-posttest Design. The research sample was 30 students. The research instrument used a scientific process skills observation sheet in the form of a checklist questionnaire. Data analysis used the Independent Sample t-test at the 0.05 significance level. The results of the research show that the science process skills of students using the PjBL model have a value of tcount 12.05 > ttable 3.98. The highest indicator was found in observations assessing and collecting data with an average of 21.6%. Overall, students' scientific process skills using the PjBL model are in the very good category (81.25%). It can be concluded that the PjBL model has an influence on the science process skills of class XI students at Dayah Insan Qur’ani, Aceh Besar.